2022
DOI: 10.3390/membranes12060590
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Silicon Doped Tin Oxide Thin Films and Thin-Film Transistors Based on Tetraethyl Orthosilicate

Abstract: Recently, tin oxide (SnO2) has been the preferred thin film material for semiconductor devices such as thin-film transistors (TFTs) due to its low cost, non-toxicity, and superior electrical performance. However, the high oxygen vacancy (VO) concentration leads to poor performance of SnO2 thin films and devices. In this paper, with tetraethyl orthosilicate (TEOS) as the Si source, which can decompose to release heat and supply energy when annealing, Si doped SnO2 (STO) films and inverted staggered STO TFTs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Si doping can also help reduce the oxygen vacancies in the metal oxide film due to its higher bond dissociation energy with oxygen (798 kJ/mol for Si–O and 547 kJ/mol for Sn–O) . Several studies have doped SnO 2 with Si and reported oxygen-vacancy suppression and improved TFT performance. , Making the film amorphous not only is relevant to achieving a uniform film quality but also allows for an easy wet etching process that can help create the pattern of the active channel layer. Additionally, the thickness values of the two films were not significantly different: 11 nm for the NH 4 NO 3 -assisted Si x Sn y O film and 9 nm for the AgNO 3 -assisted Si x Sn y O film.…”
Section: Resultsmentioning
confidence: 99%
“…Si doping can also help reduce the oxygen vacancies in the metal oxide film due to its higher bond dissociation energy with oxygen (798 kJ/mol for Si–O and 547 kJ/mol for Sn–O) . Several studies have doped SnO 2 with Si and reported oxygen-vacancy suppression and improved TFT performance. , Making the film amorphous not only is relevant to achieving a uniform film quality but also allows for an easy wet etching process that can help create the pattern of the active channel layer. Additionally, the thickness values of the two films were not significantly different: 11 nm for the NH 4 NO 3 -assisted Si x Sn y O film and 9 nm for the AgNO 3 -assisted Si x Sn y O film.…”
Section: Resultsmentioning
confidence: 99%